Contributions of multidisciplinary peer observation to reflective practices of elementary and secondary teachers - Mouraz, Ana (2016)
Reflective practices have been referred important, since last century, within teachers’ training success and teachers’ effective pedagogical action as much as they contribute to teachers’ professional development and institutional improvement. Such importance has been contributing to theory – practice relationship. Within teachers’ training contexts, this concept has different shapes as it depends of trainees and training processes’ internationalities. Reflective practices imply awareness and a critical attitude that requires an epistemological perspective. If this is not a priority, reflection risks to be superficial, as literature review shows. Within this paper, a multidisciplinary peer observation model conducted with basic and secondary teachers is evaluated. The objective is to assess the reflective potential it allows. Reports made by teachers following a multidisciplinary peer observation program were used as main data. The analysis allows concluding that model improves teachers’ self- reflection as an effect of observing process. Furthermore it is related with teachers’ community enhancement as they evolve with their peers.